Twin cervical pregnancy: a unique case report - Bassetty, Karthik Chandra; Ahmed, Rina Dutta; Fogla, Mukesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Cervical ectopic pregnancy is implantation of an embryo into the cervical mucosa below the level of the internal os. Cervical pregnancy is an infrequent form of ectopic gestation both in naturally conceived pregnancies and even after assisted reproductive technology (ART). It accounts for less than 1% of all ectopic pregnancies. The diagnosis can be missed as a case of incomplete abortion unless an experienced sonologist performs a transvaginal ultrasound. Management options vary and depend on the gestational age at diagnosis, general condition of the patient and woman’s desire to maintain fertility. Medical treatment with methotrexate is the therapy of choice in early gestation with hemodynamically stable patient. Surgical intervention is indicated in late gestation, unstable cases or failed medical treatment. At times hysterectomy is elected as the final path when bleeding does not subside. We present an unique case of twin cervical ectopic pregnancy managed initially conservatively later surgical management was undertaken in view of bleeding.